Association between serum total indoxyl sulfate, intraperitoneal inflammation, and peritoneal dialysis technique failure: a 3-year prospective cohort study - Natalia Stepanova; Victoria Driianska; Lesya Korol; Lyudmyla Snisar (BMC Nephrology)
Abstract Background The impact of protein-bound uremic toxins, specifically indoxyl sulfate (IS) on peritoneal dialysis (PD) complications remains controversial. This study aimed to explore the link between serum total IS (tIS) levels, proinflammatory cytokines in serum and peritoneal dialysis effluent (PDE), and PD technique survival. Methods In this prospective cohort study, 84 patients were followed up for three years and analyzed. Stratification into low-tIS (< 22.6 µmol/L) and high-tIS (≥ 22.6 µmol/L) groups was based on the median serum tIS concentration. Logistic regression, Kaplan-Meier, receiving operation characteristic, and Cox regression analyses assessed associations between tIS levels, cytokine concentrations (IL-6, MCP-1, TNF-α), and PD technique failure. Results Patients in the high-tIS group were older and had a higher prevalence of diabetes, a greater incidence of PD-related peritonitis, elevated diastolic blood pressure, and lower HDL cholesterol compared to those in the low-tIS group. They also exhibited higher peritoneal transport characteristics, lower dialysis adequacy, and reduced peritoneal creatinine clearance. Elevated tIS levels significantly correlated with higher PDE cytokine levels, without a corresponding rise in serum cytokine levels. Serum tIS levels ≥ 50 µmol/L predicted PD technique failure with 70.4% sensitivity and 87.9% specificity (p < 0.0001). The association between high tIS levels and PD technique failure remained significant after adjusting for confounders identified in logistic regression, including peritoneal weekly creatinine clearance, the D/P creatinine ratio, high peritoneal transport status, and PDE IL-6 and MCP-1 concentrations (HR 2.9, 95% CI 1.13; 8.21). Conclusion Our findings are the first to demonstrate a link between elevated tIS levels, peritoneal inflammation, and an increased risk of PD technique failure. Monitoring tIS levels in PD patients could be clinically relevant for risk assessment and personalized management, potentially improving long-term PD outcomes. Future research should explore interventions targeting tIS reduction to alleviate peritoneal inflammation and improve PD prognosis.